The effect of liquidity on the profitability of commercial banks in the Kingdom of Saudi Arabia Period (2010- 2019) - Abdulrahman, Najla Ibrahim; Alfarsi, Tahani Ewaed (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to identify the impact of liquidity on the profitability of commercial banks in Saudi Arabia during the period 2010 to 2019. The study was based on the descriptive analytical approach where this approach is based on data collection, description and analysis, by analyzing the financial statements of the sample banks study that will be obtained from a trading site, and then using the appropriate statistical method of data analysis based on SPSS, in order to identify the impact of liquidity on profitability. The study showed that there was a statistically significant effect at the level of liquidity (0.05) on the return on equity, while there was no effect of liquidity (trading ratio) on the return on assets. The study recommended: Saudi commercial banks should focus on aligning liquidity with profitability. to avoid falling into a financial deficit. It also needs to focus on profitability, which demonstrates the bank's ability to make profits. In addition to paying more attention to liquidity because of its impact on profitability, commercial banks also have appropriate policies to better manage their liquidity, while working to achieve profitability. Finally, work on more studies and research which are more widely available to include all banks in Saudi Arabia. Finally, some semi-liquid investments need to be maintained to ensure that there is no future liquidity crisis.
Keywords: liquidity; trading; profitability; return on assets; return on equity